2018
DOI: 10.1016/j.jhep.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

The molecular functions of hepatocyte nuclear factors – In and beyond the liver

Abstract: The hepatocyte nuclear factors (HNFs) namely HNF1α/β, FOXA1/2/3, HNF4α/γ and ONECUT1/2 are expressed in a variety of tissues and organs, including the liver, pancreas and kidney. The spatial and temporal manner of HNF expression regulates embryonic development and subsequently the development of multiple tissues during adulthood. Though the HNFs were initially identified individually based on their roles in the liver, numerous studies have now revealed that the HNFs cross-regulate one another and exhibit syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
191
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(213 citation statements)
references
References 173 publications
(235 reference statements)
4
191
1
4
Order By: Relevance
“…[64][65][66] PPAR transcription factors are known binding partners of RXR and one study predicted 17 common targets between Hnf4a and PPARa. 67 Hnf1b is expressed in all nephron segments [68][69][70][71][72] and Hnf1b deficiency in the nephron lineage of the mouse kidney leads to defects in nephron formation, particularly the proximal tubules, loops of Henle, and distal tubules. 72,73 Hnf1b is known to interact with Hnf4a and regulate common target genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64][65][66] PPAR transcription factors are known binding partners of RXR and one study predicted 17 common targets between Hnf4a and PPARa. 67 Hnf1b is expressed in all nephron segments [68][69][70][71][72] and Hnf1b deficiency in the nephron lineage of the mouse kidney leads to defects in nephron formation, particularly the proximal tubules, loops of Henle, and distal tubules. 72,73 Hnf1b is known to interact with Hnf4a and regulate common target genes.…”
Section: Discussionmentioning
confidence: 99%
“…72,73 Hnf1b is known to interact with Hnf4a and regulate common target genes. 67,69,74 It has also been shown that expression of Hnf1b and Hnf4a, along with Emx2 and Pax8, can convert fibroblasts into renal tubular epithelial cells, strongly suggesting that Hnf1b is a co-regulator of proximal tubule development. 75 Further investigation is needed to elucidate the interactions among these transcription factors and their roles in proximal tubule development.…”
Section: Discussionmentioning
confidence: 99%
“…HNF4α and HNF1α were identified as among the six master regulators for human hepatocytes, using chromatoimmuno-precipitation and high-resolution promoter microarrays [22]. Both of them can activate each other as well as positively auto-regulate themselves [18,22]. Their expression levels are lower in fatty liver disease patients as compared to healthy controls [16].…”
Section: Identification Of a Core Hnf4α-pparγ Network In Hepatocytesmentioning
confidence: 99%
“…Hepatocyte Nuclear Factor 1α (HNF1α) [16][17][18]. HNF4α is an established master regulator of induction and maintenance of the hepatic cell state [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these functions are carried out by hepatocytes (Fraczek et al 2013). At the most upstream regulatory level of gene expression, the production of the mediators of hepatocyte functionality is controlled by the orchestrated interplay between liver-enriched transcription factors and nuclear receptors (Lau et al 2018). Accordingly, demonstration of hepatocyte functionality could start by testing expression of these liver-enriched transcription factors, such as CCAAT/enhancer-binding protein alpha, hepatocyte nuclear factors 1 alpha and 4 alpha, and nuclear receptors, like the constitutive androstane receptor and the pregnane X receptor, as well as of the functionality mediators as such.…”
Section: Functionalitymentioning
confidence: 99%